Panorama intelectual de la terminología a través del análisis de redes sociales - Castro-Prieto, María; Olvera Lobo, María (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2007)
AbstractWhen transmitting scientific knowledge, authors weave a web of intellectual affinities through the works they cite that portrays trends and developments in research in their discipline. In the present article, we aim to establish an intellectual panorama of Terminology in which we depict the outstanding developments in research and the most influential authors. To do so, we analyze periodical publications that have appeared over a wide period of time. Author Citation Analysis (ACA) and the visual representation of the relationships between authors through social networks (specifically, pathfinder networks) is based on the premise that links are necessarily established between the authors cited in any specific work so that greater frequency of co-ocurrence indicates a stronger affinity between authors. Among other findings, our results show that the group of most frequently cited authors represents less than 1% of the total and that only 12% of authors have published three or more articles. Moreover, we can confirm that research in Terminology is developing in three clearly differentiated directions: theoretical foundations, Natural Language Processing and Socioterminology.